Perancangan strategi promosi untuk meningkatkan kunjungan workshop gerabah - Valiana, Veronika Nadiya; Hadisantono; Hanandoko, Theodorus B. (Jurnal Teknik Industri dan Manajemen Rekayasa, 2025)
Background: UMKM X is a small-medium enterprise engaged in educational pottery tourism in the Kasongan area. The low number of workshop visits is caused by the absence of a targeted promotional strategy, as promotion has so far relied solely on word of mouth. Methods: The promotional strategy design began with a SWOT analysis to evaluate the internal and external conditions of the SME, followed by determining Segmenting, Targeting, and Positioning (STP), as well as selecting promotional methods using the Promotion Mix. Based on agreements with stakeholders, the chosen strategies included direct marketing via email and WhatsApp messages with leaflets and collaboration proposals, supported by social media marketing through the creation of a company profile video to be uploaded on Instagram. Results: The six-month implementation (January–June 2025) included the creation of workshop package catalogs, collaboration proposals for schools and travel agents, as well as a company profile video for brand awareness. This strategy successfully increased the average number of visits by 50%, from four visits/month to six visits/month. Conclusion: The designed promotional strategy proved to be effective and exceeded the established critical success factor (CSF), making it adaptable for similar SMEs.